أثر تقلبات أسعار الصرف على النمو الإقتصادي - رابح, رضوان (My University, 2019)
The exchange rate and economic growth are considered as the most important economic indicators reflecting The country’s economy for in the world. The objective of this study is to study the effect of the exchange rate on economic growth and the reality on the Algerian economy during the period( 2010- 2017). we use the analytical descriptive approach in order to achieve the objectives of this study. The findings show the existence of a negative impact of The exchange rate on economic growth in Algerian within inflation, money supply and government spending as regulator variables, as well as the exchange rate market that amplifies the magnitude of this effect.
الجزائر 2010-2017
Keywords: اسعار الصرف،سعر الصرف الحقيقي، النمو الاقتصادي، الجزائر